Hexavalent Chromium Reduction by Ferrous Sulphate Heptahydrate Addition into the Portland Clinker. (2016) - Mončeková, Miroslava; Novotný, Radoslav; Koplík, Jan; Kalina, Lukáš; Bílek, Vlastimil; Šoukal, František
Abstract: Nowadays, hexavalent chromium and its content in Portland cement is very actual and often discussed topic. The goal of this study was to observe the influence of different ways of addition of ferrous sulphate heptahydrate on the reduction of hexavalent chromium at the hydration of Portland clinker. Ferrous sulphate heptahydrate was added as crystalline powder and also in an aqueous solution. Obtained experimental results clearly showed higher reduction ability of a liquid form compared to the solid substance. The influence of the grain size on the reduction of hexavalent chromium was investigated immediately after mixing clinker with water and also during the first days of hydration process. New oxidation layer containing Fe 3+ species forms around the non- oxidation part of sulphate species. That is why larger grain size showed lower reduction ability of chromium. In this case the additional chromium reduction effect was observed during the first days of hydration. The results were acquired by UV/VIS method according to STN EN 196-10.